Poems around Calcetta - Carnice, F. Jordan (Likhaan: The Journal of Contemporary Philippine Literature; Vol 17 No 1 (2023): LIKHAAN 17: The Journal of Contemporary Philippine Literature, 2023)
In Poems Around Calcetta, the microcosm stands in for the big picture through a fictionalized version of the author’s hometown in Bohol. Both historical events and ordinary everyday coincidences of a place are (re)imagined to tackle issues on the climate crisis and environmental decline, progress at the expense of preservation, and the increasing neglect of sound political decisions. Through this mini suite of poems, the provincial proves to be universal, and wherever one is situated in this world, the consequences of our decisions and of our state are just trailing behind us, or worse, already in front of us.